2012
DOI: 10.5539/ijbm.v7n2p163
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Successful Adoption of Decision Support Systems: The Context of Aqaba Special Economic Zone Authority

Abstract: This research aimed to examine the main factors that influence the successful adoption of Decision Support

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…Moreover, Ketikidis et al [13] found that perceived ease of use has directly predicted health IT usage intentions. However, this finding is not consistent with Aldhmour and Eleyan [2] who reported contradictory results about the impact of perceived ease of use.…”
Section: Key Findingscontrasting
confidence: 93%
See 4 more Smart Citations
“…Moreover, Ketikidis et al [13] found that perceived ease of use has directly predicted health IT usage intentions. However, this finding is not consistent with Aldhmour and Eleyan [2] who reported contradictory results about the impact of perceived ease of use.…”
Section: Key Findingscontrasting
confidence: 93%
“…Technology acceptance model was used in previous research to predict users' acceptance and adoption of new technologies including DSSs [16,17,18,19,2]. In the present study, we developed a model to investigate and predict nursing staff acceptance of mobile DSS.…”
Section: Hypotheses Buildingmentioning
confidence: 99%
See 3 more Smart Citations